Enhancing financial citizenship through financial technology: a systematic literature review - Rupali Kumari; Mugdha Kulkarni (Cogent Economics & Finance)
This study seeks to integrate the most recent research surrounding financial citizenship and financial technology (FinTech) to highlight their role within contemporary financial systems in promoting economic equity and transforming financial services in practice. Data were systematically collected from the databases- Scopus and Web of Science using the PRISMA method. A bibliometric analysis was performed using Biblioshiny on the open-access documents. The review concluded that financial citizenship, which consists of financial inclusion, literacy, financial protection and financial trust, is the key to advancing economic equality and democratic participation. This study contributes to both the financial citizenship and financial technology bodies of knowledge by conducting a comprehensive review of the current literature, linking the two areas of research that are usually seen separately. The study brings a unique perspective in understanding the implications of technology concerning financial inclusion and stability and identifies important aspects that call for future research.